เปรียบเทียบความหมายของคําประสมระหว่างภาษาไทยและภาษาอังกฤษเพื่อการแปล - อังสุวรรณ, วิมลวรรณ (Journal of the Faculty of Arts, Silpakorn University, 2020)
This article aims at comparing Thai compound words with English compound words. The data were collected from Thai juvenile literature. According to the data, both Thai and English compound words have specific meanings which are in accordance with the meaning of the main word, the implied meaning of both words, and conceptual meaning. The meaning which indicates characteristics or manner and metaphorical meaning are found only in Thai compound words. In addition, the Thai compound words structure is different from English compound words. Thai compound words structure consists of a main word and a compound; on the other hand, English compound words structure consists of a compound and a main word. As a result of this, when translating English into Thai or Thai into English, the translator should be concerned with both the meaning and structure of the compound words for accurate, communicative and natural translate.